2010
DOI: 10.1380/ejssnt.2010.241
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electronic Structure of Imidazolium-Based Ionic Liquids Studied by Electron Spectroscopy

Abstract: We have measured the bulk and surface electronic structure of several ionic liquids of alkyl-imidazolium cations with different alkyl chains (EMIm, BMIm, HMIm, OMIm) and bis(trifluoromethylsulfonyl)imide anions (Tf2N) by X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS He I and He II) as well as metastable induced electron spectroscopy (MIES). The results are compared with the densities of states (DOS) calculated by density functional theory (DFT). By XPS we found the stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…However, as the present XPS results for [OMIm]Tf 2 N on copper are in good agreement with XPS studies in the literature 26,[29][30][31] and as there are no further chemical changes visible, bulk interactions between [OMIm]Tf 2 N and copper can be neglected. .…”
Section: Reference Spectrum Of [Omim]tf 2 N On Cusupporting
confidence: 91%
“…However, as the present XPS results for [OMIm]Tf 2 N on copper are in good agreement with XPS studies in the literature 26,[29][30][31] and as there are no further chemical changes visible, bulk interactions between [OMIm]Tf 2 N and copper can be neglected. .…”
Section: Reference Spectrum Of [Omim]tf 2 N On Cusupporting
confidence: 91%
“…Figure 5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 123 They observed that the peak at approximately 7 eV starts to grow at a coverage greater than one monolayer and is shifted to a higher binding energy toward the bulk IL value, indicating that this peak is derived from the electronic states of the randomly oriented IL not directly in contact with the metal substrate. Because the peak positions of bulk UP-spectra of BMIM-TFSI and EMIM-TFSI are similar, 122 we consider that the peak at approximately 7 eV observed in this study can be attributed to the randomly oriented IL on ferrocene-terminated SAMs. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 ...…”
Section: Methodsmentioning
confidence: 61%
“….n ) in our calculation (see Table 1 and Fig. 1 ), which contribute to the peak at 283.52 eV (285.2 eV in the experiment 1,27 ), and carbon atoms directly attached to nitrogen atoms in the imidazoliumring (C . Notably, the calculated contributions of the carbon atoms C 1 -C 3 (see Fig.…”
Section: Results and Discussion Xps Core Level Spectramentioning
confidence: 79%
“…In the experimental spectra this effect is indicated by a shift of the respective peak with the increasing length of the alkyl-chain. 1,27,57 Finally, we have to note that like for the N1s core levels the calculated energy difference between the C1s peaks attributed to the [Tf 2 …”
Section: Results and Discussion Xps Core Level Spectramentioning
confidence: 96%
See 1 more Smart Citation